Pengaruh Pemanfaatan Teknologi Informasi dan Penyajian Materi Ajar terhadap Minat Belajar Siswa SMP YPJ Kuala Kencana - Marisa, Riandi; Matelda Alfonsina Ibo; Bernada Materay (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the dynamics of the population and sample of students at SMP YPJ Kuala Kencana and to understand the distribution patterns of students used in the study. The main focus of this study is to identify the number of active students and those used as research samples, especially in March 2025. The research method used is a quantitative approach with a descriptive design. Data collection techniques are carried out through documentation obtained directly from school administrators. The data collected are then analyzed using quantitative descriptive analysis techniques to describe the population and sample patterns used. The results of the study showed that the total number of active students at SMP YPJ Kuala Kencana in March 2025 was 210 students, consisting of 65 students in grade 7, 68 students in grade 8, and 77 students in grade 9. In this study, only students in grades 8 and 9 were used as research samples, with a total sample size of 145 students. The selection of full samples for grades 8 and 9 was based on certain considerations related to the objectives of the study, while grade 7 was not included in the sample. These findings provide a clearer picture of the distribution of students and the approach used in sampling in the school environment. The conclusion of this study is that the distribution of samples at SMP YPJ Kuala Kencana has been carried out systematically by considering the number of active students at each grade level. The results of this study can be the basis for further research in understanding the academic dynamics at the school and as a reference in developing more effective educational strategies.